2014
DOI: 10.7731/kifse.2014.28.5.030
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Air Egress Velocity in Vestibule Pressurization System : Characteristics of Air Flow in the Vestibule with Multiple Fire Doors in an Apartment Building

Abstract: The pressurized smoke control system in the vestibule is important for fire safety in buildings because it is concerned with egress time of people and the safety of fire fighters. The vestibule pressurization system can prevent smoke from entering the vestibule using differential pressure when fire doors are closed and using the egress velocity when fire doors are open. Air supplying units in the vestibule need to be arranged by taking account of the location of doors and the volume of the vestibule in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…They found that in the case upward 45 gradient of supply damper's blade, the simulation results that air flow of upper vestibule is steady but back-flow phenomenon occurred at the bottom. Seo and Shin [11,12] investigated the characteristics of air flow in the vestibule with multiple fire doors in an apartment building and the damper location for uniform air egress velocity in the case of two fire doors by using the method of CFD numerical simulation. Their research found that when the damper in the vestibule is located at the center of the wall opposite to two fire doors, the uniform air egress velocity can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…They found that in the case upward 45 gradient of supply damper's blade, the simulation results that air flow of upper vestibule is steady but back-flow phenomenon occurred at the bottom. Seo and Shin [11,12] investigated the characteristics of air flow in the vestibule with multiple fire doors in an apartment building and the damper location for uniform air egress velocity in the case of two fire doors by using the method of CFD numerical simulation. Their research found that when the damper in the vestibule is located at the center of the wall opposite to two fire doors, the uniform air egress velocity can be obtained.…”
Section: Introductionmentioning
confidence: 99%